1964
DOI: 10.1037/h0042567
|View full text |Cite
|
Sign up to set email alerts
|

Critical periods, stimulus input, and emotional reactivity: A theory of infantile stimulation.

Abstract: Experiments, using rats and mice, do not support the critical period hypothesis that there are certain limited time periods in infancy during which a particular class of stimuli will have profound effects upon subsequent behavior. Where findings are consistent with the hypothesis, further research has shown that the "critical period" is a complex function of amount of infantile stimulation. The central hypothesis of this paper is that amount of stimulus input in infancy acts to reduce emotional reactivity in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
188
2
3

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 421 publications
(215 citation statements)
references
References 56 publications
22
188
2
3
Order By: Relevance
“…The classical studies of Denenberg, Levine, and colleagues showed that postnatal handling decreased the expression of fearrelated behaviors under stressful conditions (see Denenberg 1964;Levine 1975). More recent studies have shown that these effects are particularly notable under conditions of novelty (e.g., Bodnoff et al 1987;Nunez et al 1996;Escorihuela et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The classical studies of Denenberg, Levine, and colleagues showed that postnatal handling decreased the expression of fearrelated behaviors under stressful conditions (see Denenberg 1964;Levine 1975). More recent studies have shown that these effects are particularly notable under conditions of novelty (e.g., Bodnoff et al 1987;Nunez et al 1996;Escorihuela et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The development of behavioral and endocrine responses to acute stress is greatly influenced by the early postnatal rearing environment (for reviews see Levine 1975;Denenberg 1964;Meaney et al 1996). These environmental effects persist throughout the life of the animal, resulting in stable individual differences in stress reactivity.…”
Section: We Compared the Effects Of Handling Or Maternal Separation Fmentioning
confidence: 99%
See 3 more Smart Citations